Влияние запаздывания по измерению частоты вращения на показатели регулирования мощной дизель-генераторной установки - Богаевский, Александр Борисович; Борисенко, Анатолий Николаевич; Кубрик, Борис Иванович; Литвиненко, Светлана Анатольевна; Борисенко, Евгений Анатольевич (НТУ "ХПИ", 2016)
Проведено исследование влияния запаздывания по измерению частоты на показатели устойчивости и точности регулирования мощной дизель-генераторной установки с импульсным датчиком частоты в обратной связи. Использованы методы теории нелинейных импульсных систем автоматического управления и моделирование переходных процессов системы регулирования. На основании критерия Найквиста определено минимально допустимое число зубьев в измерительной шестерне. Получены практические выражения по определению числа зубьев для обеспечения требуемой точности регулирования.

The effect of the delay on the measurement of frequency stability performance and control accuracy powerful diesel-generator set with a pulse frequency sensor feedback. Methods of the theory of nonlinear pulse systems of automatic control and modeling of transition processes of system of regulation are used. On the basis of the Nyquist criterion to determine the minimum allowable number of teeth in the measuring gear. Modeling of processes of regulation of frequency in system on the model created in the environment of Simulinc was carried out. Cases of transition processes in the closed system for various quantity of teeths in a measuring gear wheel were modelled.Get practical expression to determine the number of teeth to provide the desired control accuracy.
A delay effect on the measurement of speed indicators on control powerful diesel generator set
Keywords: запаздывание; устойчивость; число зубьев; измерительная шестерня; frequency; precision control; measuring gear